Using informative assessments towards effective literacy practices - Ortlieb, Evan.; Cheek, Earl H. (Bingley, U.K. : Emerald, 2012)
Utilizing Informative Assessments towards Effective Literacy Instruction offers research driven solutions to improving student literacy success through the exploration of advancements in literacy assessment and instruction. As the first volume in the series, Literacy Research, Practice, and Evaluation, distinguished authors share a comprehensive portrayal of why assessments are necessary, how to select appropriate assessments, and how to effectively use data for curricular planning and instruction. By addressing concerns before, during, and after literacy instruction with research-based instructional techniques embedded within the chapters, readers garner rich perspectives on literacy assessment that can immediately impact their effective teacher practices. This text is founded on the principle that praxis, or the combination of research with practice, should be the ultimate goal of educational missions and visions alike. It provides a fresh examination of current issues and trends in literacy assessment salient to novice and experienced educators alike.
Introduction / Evan Ortlieb -- Inquiry-based formative assessment for improving student learning / Kathleen Wilson, Robert Calfee -- Making the most of informal reading inventories : moving from purposeful assessment to targeted instruction / Jerry L. Johns, Susan K. L'Allier, Beth Johns -- Using formal assessments to guide instruction / Daniel L. Pearce, Wolfram E. Verlaan -- Using systematic observation to assess early literacy development and plan instruction / Emily Rodgers -- Selecting appropriate individual and group-based assessments / Evan Ortlieb, Earl H. Cheek, Erica Bowers, Gerlinde Grandstaff-Beckers -- Matching our knowledge of reading development with assessment data / Danielle V. Dennis -- Using informative assessments for effective literacy practices / Doris Walker-Dalhouse, Victoria J. Risko -- Assessing special populations of students / Fabiola P. Ehlers-Zavala -- The assessment to instructional planning (ATIP) framework : a multidimensional, contextualized approach to using assessment to plan instruction / Laurie Elish-Piper, Susan Hinrichs, Samantha Morley, Molly Williams -- Effective and efficient : maximizing literacy assessment and instruction / Kathleen A.J. Mohr, Kathryn Dixon, Chase Young -- Addressing the literacy needs of striving readers / J. Helen Perkins, Crystal D. Cook -- Strategies for differentiated instruction for English learners / Shelley Xu -- Evaluation : an eye-opening experience / Mayra C. Daniel, James Cohen.
Keywords: Education -- Evaluation; Education -- Teaching Methods & Materials -- General; Literacy strategies; Curriculum planning & development; Literacy -- Evaluation; Language arts -- Ability testing; Literacy